Instilling Local Wisdom’s Value in the Learning of Social Studies as an Effort to Increase Social Awareness of Junior High School Students - Sugiantoro Sugiantoro; Joko Widodo; Masrukhi Masrukhi; Agustinus Sugeng Priyanto (Universitas Negeri Semarang, 2021)
Social studies learning contributes to social and human values. This study relates to the value of local wisdom in social studies learning in Sidoarjo Regency in order to increase the social awareness of junior high school students. This study aims to determine the inculcation of local wisdom values ​​through planning, implementation, and student responses to the value of local wisdom in social studies learning. This study uses qualitative methods and research data sourced from primary and secondary data. Data collection techniques were carried out through observation, interviews, and documentation. Validity test using triangulation technique. Data analysis uses interactive analysis, namely through data reduction, data presentation, and data verification. The results showed that 1) the learning design prepared by the teacher was appropriate and categorized as good, 2) the implementation of the value of local wisdom in social studies learning was able to improve students' conceptual understanding, 3) student responses to social studies learning carried out by teachers combined with local wisdom were able to foster enthusiasm. because students can understand the material based on their experience. In conclusion, the inculcation of local wisdom values ​​in social studies learning is able to increase learning motivation and develop students' social care attitudes.